Analysis of the Phenomenon of ChatGpt Usage on the Creativity of Thinking of Today's Students in Indonesia - Madar, Paulus; Mufti, Zulfikar (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This study explains how ChatGpt, which is a sophisticated technology today, is used by Indonesian students to work on various problems on campus, especially in completing daily and final assignments. However, the use of ChatGpt is considered to be able to affect the creativity of thinking of every student who uses it. ChatGpt will limit the creativity of thinking of students because its users will depend on ChatGpt, while ChatGpt has limitations where ChatGpt only depends on the algorithm, so it will only display what is in the algorithm. Through a qualitative case study approach, this study will present and explain the use of ChatGpt by Atma Jaya University Informatics Study Program students in their lectures as well as presentations on the use of ChatGpt, and also present presentations on the use of ChatGpt in the academic world from each generation. From the data displayed, the use of ChatGpt by students will be analyzed which can limit their creativity of thinking in lectures.